(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This article frames the Spanish economic crisis in the context of the international financial crisis, explains its impact on the Spanish financial sector, the measures taken to restructure the sector and finally reflects upon the sector’s positioning forthe near future.